If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + -4) + 1 = 3(x + -3) Reorder the terms: 5(-4 + x) + 1 = 3(x + -3) (-4 * 5 + x * 5) + 1 = 3(x + -3) (-20 + 5x) + 1 = 3(x + -3) Reorder the terms: -20 + 1 + 5x = 3(x + -3) Combine like terms: -20 + 1 = -19 -19 + 5x = 3(x + -3) Reorder the terms: -19 + 5x = 3(-3 + x) -19 + 5x = (-3 * 3 + x * 3) -19 + 5x = (-9 + 3x) Solving -19 + 5x = -9 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -19 + 5x + -3x = -9 + 3x + -3x Combine like terms: 5x + -3x = 2x -19 + 2x = -9 + 3x + -3x Combine like terms: 3x + -3x = 0 -19 + 2x = -9 + 0 -19 + 2x = -9 Add '19' to each side of the equation. -19 + 19 + 2x = -9 + 19 Combine like terms: -19 + 19 = 0 0 + 2x = -9 + 19 2x = -9 + 19 Combine like terms: -9 + 19 = 10 2x = 10 Divide each side by '2'. x = 5 Simplifying x = 5
| x^3-2x^2-4x-6=0 | | 13-9x=108-44x | | x+4(16)=16 | | -26.34+42.18=x | | 4xX=6 | | 45=9*1 | | 5+2y-2=9y+12-6y | | 17x+8+9x-9=2x+23 | | 3x+1/3-13/2=1-x/4 | | 2(x-3)=-10 | | -14=8+x | | 2-5(3-y)=2-(4-5y) | | 48=2x-6 | | 1=5p-2-4p | | 4=7x | | 2(6-8x)=4(2x-3) | | -11x+22=45 | | r+0.27=-0.59 | | 6(-x-2)=48 | | r+0.27=-0.25 | | -7x+6=48 | | 2(x+1)=3(x+7)-12 | | 2x/3=6-x/4 | | 25x^2-129=0 | | 3(2+x)=2(2+x) | | x^3+10x^2+13x+24=0 | | 2(x+1)=3(x+7) | | x-2(6)=2 | | 3s^2=2s^2+1 | | 5x+4=-x-20 | | -10x-4x+13x=0-7 | | 5x-7(x-4)=51 |